Hearing Ability in Orchestral Musicians - PAWLACZYK-ŁUSZCZYŃSKA, Małgorzata; DUDAREWICZ, Adam; ZAMOJSKA, Małgorzata; ŚLIWIŃSKA-KOWALSKA, Mariola (Archives of Acoustics, 2010)
Pure-tone audiometry (PTA) and transient-evoked otoacoustic emissions (TEOAEs) were determined in 57 classical orchestral musicians along with a questionnaire inquiry using a modified Amsterdam Inventory for Auditory Disability and Handicap ((m)AIADH). Data on musicians’ working experience and sound pressure levels produced by various groups of instruments were also collected. Measured hearing threshold levels (HTLs) were compared with the theoretical predictions calculated according to ISO 1999:1990. High frequency notched audiograms typical for noise-induced hearing loss were found in 28% of the subjects. PTA and TEOAE consistently showed a tendency toward better hearing in females vs. males, younger vs. older subjects, and lower- vs. higher-exposed to orchestral noise subjects. Audiometric HTLs were better than theoretical predictions in the frequency range of 2000-4000 Hz. The (m)AIADH scores indicated some hearing difficulties in relation to intelligibility in noisy environment in 26% of the players. Our results indicated a need to implement a hearing conservation program for this professional group.